Analisis Sistem Drainase Pada Kawasan yang Terdampak Banjir di Daerah Panembong - Tutin Mustaatinah; Sulwan Permana (Jurnal Konstruksi, 2026)
Flooding is a natural disaster that frequently occurs in Indonesia. One of the main causes of flooding is the inability of drainage channels to convey water effectively and efficiently. One area that often experiences flooding is Kampung Nangoh, Panembong Village. The factors causing flooding in this area include low-lying topography, accumulated waste, sedimentation buildup in the channels, and inadequate drainage maintenance systems. To address flooding problems, a drainage system analysis is required. This analysis involves calculating the design flood discharge and determining channel dimensions capable of accommodating the planned discharge. The results of the study show that the design flood discharges for return periods of 2, 5, 10, 25, and 50 years using the Normal method are 14.48222 m³/s, 16.3194 m³/s, 17.2351 m³/s, 18.1285 m³/s, and 18.7163 m³/s, respectively. Using the Log Normal method, the design flood discharges are 14.4588 m³/s, 16.0149 m³/s, 17.0230 m³/s, 18.1053 m³/s, and 18.8757 m³/s, respectively. The channel dimensions capable of accommodating the design flood discharge using the Normal method for return periods of 2, 5, 10, 25, and 50 years are 2 × 1 m, 2 × 1 m, 2 × 1 m, 2.2 × 1.1 m, and 2.2 × 1.1 m, respectively. For the Log Normal method, the required channel dimensions for return periods of 2, 5, 10, 25, and 50 years are also 2 × 1 m, 2 × 1 m, 2 × 1 m, 2.2 × 1.1 m, and 2.2 × 1.1 m, respectively.